Portfolio optimization in the catastrophe space. (18th May 2020) - Chang, Carolyn W.; Chang, Jack S. K.; Yu, Min‐Teh; Zhao, Yang
Abstract: In today's global catastrophe space, the role of insurance‐linked securities has evolved from that of a threatened reinsurance substitute to now being a viable complementary reinsurance product, underpinning the convergence of the two markets. This study constructs a two‐agent sequential optimization framework to mimic the economics of the reinsurance/insurance markets and shows how NPV‐maximizing reinsurers and hedging cost‐minimizing insurers can optimally allocate default‐risky catastrophe reinsurance and default‐free catastrophe bonds at the interface of these two markets. We analyze parametric impacts considering interest rate risk, financial leverage, basis risk, differential markup, catastrophe arrival intensity, and severity, as well as other relevant characteristics.